2020
DOI: 10.1016/j.ebiom.2020.102793
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic reconstruction of breast cancer reveals two routes of metastatic dissemination associated with distinct clinical outcome

Abstract: Background: In breast cancer (BC), axillary lymph node (ALN) involvement is one of the strongest adverse prognostic factors. However, it is unclear whether loco-regional lymph node deposits are effectively the root of secondary metastases or only an indicator of competence of the primary tumour to spread to distant organs. Methods: Here, we investigated the evolutionary trajectories of primary tumour, ALN and distant metastasis samples from 16 estrogen-receptor (ER)-positive lymph node-positive BC patients. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
1
22
0
2
Order By: Relevance
“…In addition, lymph nodes formed an independent clade with a few mutations shared between the primary treatment-naïve tumor and other lesions, suggesting that spreading may occur early in these tissues. This same pattern has been reported in other molecular studies [13,32,47]. Clinical and molecular analyses in TNBC and breast cancer have also shown dissemination to lymph nodes from small T1 tumors (<2 cm), and the occurrence of metastatic spread in the early stages of tumor growth [48][49][50].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, lymph nodes formed an independent clade with a few mutations shared between the primary treatment-naïve tumor and other lesions, suggesting that spreading may occur early in these tissues. This same pattern has been reported in other molecular studies [13,32,47]. Clinical and molecular analyses in TNBC and breast cancer have also shown dissemination to lymph nodes from small T1 tumors (<2 cm), and the occurrence of metastatic spread in the early stages of tumor growth [48][49][50].…”
Section: Discussionsupporting
confidence: 82%
“…In 213 samples from 17 patients with colorectal cancer only 35 percent of distant metastases shared a common sub-clonal origin as the LN metastases, which is expected for a cancer that particularly favors hepatic metastasis via the portal vein (Naxerova et al, 2017). However, what is surprising are the findings of Venet et al, who showed that in estrogen receptor positive breast cancer, 75 percent of the distant metastasis did not share a common clonal origin with the axillary LN (Venet et al, 2020).…”
Section: Metastasismentioning
confidence: 97%
“…35 Accordingly, clinical evidence of self-seeding 36 whereby a metastatic cell re-infiltrates its primary tumour-and of metastasis-to-metastasis spread 37,38 has been documented, with one such study in HR + breast cancer patients reporting a common origin between lymph node and distant metastases in up to 25% of cases. 39 When do tumour cells disseminate? Early versus late dissemination The first step of the metastatic cascade refers to the ability of cancer cells to escape from the primary tumour.…”
Section: Disseminated Tumour Cells As Culprits For Metastatic Recurrencementioning
confidence: 99%